Caracterização do estado polaron do polipirrol através de raman e propriedades fotoluminescentes do polipirrol/oxazina 720 - Santos, Marcos José Leite (2009)
This doctor degree project had as initial objective the structural and optical characterization of polypyrrole (ppy) films embedded with molecules of the laser dyes oxazine 720, LDS 821, Coumarin 522 and Coumarin 480, aiming its application in organic light emitting devices (OLED). These laser dyes were divided m two groups: 1) oxazine 720 and LDS 821, the dyes are both excited at around 633 nm, and are cationic salts; 2) Coumarin 480 and Coumarin 522, the dyes are excited at around 514 nm, and are neutral molecules (it implies in different interactions, between ppy and dye, comparing to group 1). However, only the ppy/oxazine 720 and the ppyfLDS 821 films presented interesting opticai properties with potential application in OLED. The results presented in this thesis is focused on the structural and optical properties of ppyloxazine 720 (ppy/oxa) and in the elucidation of the mechanism by which the laser dye emission is controlled by the eiectric and structurai properties ofthe polypyrrole fim at different oxidation levei. The obtained results shows jthat the light emitting properties ofppy/oxa films are not intrinsic to the conjugated polymer, unlike Iworks published so far. The laser dye embedded polypyrrole films were electrochemically synthesized. The electrical, optical, and structural properties of the films were characterized by cyciic voltammetry, UV-Vis and Raman spectroscopies, fluorescence and excited state lifetime measurements. Ali the spectroscopic measurements were performed with in situ electrochemistry aiming the study of optical and structural changes at different oxidation leveis. Durmg the structurai characterization it was observed that the ppy present characteristic vibration modes for oxidized and reduced states. However, at intermediary oxidation leveis, the vibration modes of both benzoid (reduced state) and quinoid (oxidized state) forms are observed m the Raman spectrum. This mtermediary state was assigned to the polaron state. By the Raman spectrum of pure ppy it was possible to determine the potential range where the polaron and the bipolaron states are present. This was the first time that the polaron and bipolaron forms were observed by structural measurements.